ANALISIS FAKTOR PENDUKUNG KEMENANGAN CALON LEGISLATIF PEREMPUAN PARTAI GOLONGAN KARYA DI DAERAH PEMILIHAN III KABUPATEN KARIMUN PROVINSI KEPULAUAN RIAU TAHUN 2014 - Azhima, Fauzan; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The existence of woman in Indonesia parliament is still far from insufficient. Woman Legislators either in central or region of parliament has not indicate any significant growth. The electoral support is become one of the capital required of woman candidates to compete in elections. In Karimun, a region from Province of Riau Island recorded only three candidates were succeed to become the legislator as one of them able to achieve significant vote. Based on the background of these problems researcher interested to conduct more in-depth study on “Winning Factor of a Woman Candidate Golongan Karya Party in District III Karimun Region Riau Island Province”. The method used in this study is a qualitative research method. From the research that has been made known that the required capital with a good management could make a candidate take the victory in Legislative Election. The capital is divided into three part as known as social capital, political capital, and economic capital.The three based capital with prudent management is able to give victory to candidates. Keywords : Candidate, Capital , Parliamentary, Woman